2011
DOI: 10.1016/j.ausmj.2011.07.004
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Romance: The Technology Acceptance Model with Emotional Attachment

Abstract: E-readers, or devices designed primarily for reading e-books, are taking the world by storm. Several papers in library studies and education have examined e-book consumption for academic reading. However, no previous marketing study has investigated consumers’ adoption of e-readers for pleasure reading. We address this gap by testing an extended version of the Technology Acceptance Model (TAM) with emotional attachment (TAME) in this context. Consumers’ attachment to paper books is proposed as a barrier to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 24 publications
2
74
0
9
Order By: Relevance
“…Research on the individual use of technology has identified a link between emotional attachment to a technology and enjoyment derived from using that technology (Read, Robertson, & McQuilken, 2011). This is in part because when someone is emotionally attached to a technology, that person is much more likely to enjoy employing that technology (Roto & Rautava, 2008).…”
Section: Team Emotional Attachment and Team Visibilitymentioning
confidence: 99%
“…Research on the individual use of technology has identified a link between emotional attachment to a technology and enjoyment derived from using that technology (Read, Robertson, & McQuilken, 2011). This is in part because when someone is emotionally attached to a technology, that person is much more likely to enjoy employing that technology (Roto & Rautava, 2008).…”
Section: Team Emotional Attachment and Team Visibilitymentioning
confidence: 99%
“…While the emotional attachment created through individuals forming bonds with their smartphones (an inanimate object) was found to be an important factor, further research 445 should be carried out to extend the original TAM, given its focus on cognition at the expense of consumer emotion (Read, Robertson, & McQuilken, 2011). In particular, there needs to be a further analysis of moderating variables (gender, previous ICT experience) and an exploration of the importance of facilitating conditions (the degree to which an individual believes that an organizational and technical infrastructure exists to support the use of smartphones).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Group norms were measured using the 2-item scale developed by Zhou (2011). Finally, we modified four items from Read, Robertson and McQuilken (2011) to measure continued usage intention. All items were measured using a 7-point Likert scale (ranging from 1 = strongly disagree, to 7 = strongly agree).…”
Section: Measurementsmentioning
confidence: 99%